ChemInform Abstract: Copper‐Catalyzed Oxidative Ring Closure and Carboarylation of 2‐Ethynylanilides. Issue 16 (22nd April 2014) - Sinai, Adam; Meszaros, Adam; Gati, Tamas; Kudar, Veronika; Pallo, Anna; Novak, Zoltan
Abstract A new copper‐catalyzed oxidative ring closure of ethynyl anilides with diaryliodonium salts is developed for the highly modular construction of benzoxazines bearing a fully substituted exo double bond.